THE ALTITUDINAL, CLIMATICAL AND PHENOLOGICAL CLASSIFICATION OF VERBASCUM L. SPECIES FROM DIFFERENT PHYTOGEOGRAPHICAL REGIONS OF TURKEY - Karaveliogullari, F. A.; Celik, S.; Isik, G. (CORVINUS UNIV BUDAPEST, 2016)
The Verbascum L. Group A with 4 stamens (30 taxa) were grouped which encompass ecological range, climatic specificity (temperature and precipitation), altitude and phenology (flowering and seed bearing periods) in Irano-Turanian, East Mediterranian and Euro-Siberian phytogeographical regions in Turkey. For this purpose Single Linkage (Nearest Neighbour) Hierarchical Cluster method was used. The results of cluster analyses suggested that the plant species which were collected from Irano-Turanian, East Mediterranean and Euro-Siberian regions might be divided into three groups with respect to 5 characteristics based on cophenetic correlation, Delta coefficient, the pooled standard deviation of all the variables forming the cluster (RMSSTD) and determination coefficient (R-2). Pearson correlations were also computed in order to investigate linear relations between the phenological characteristics of regions. It was observed that there was a negative relation between temperature and flowering time (r=0.678; p=0.008), temperature and seed bearing time (r=-0.657; p=0.011) in Irano-Turanian region. However, the correlation between temperature and flowering time (r=-0.096; p=0.767) and temperature and seeding time (r=0.176; p=0.584) was not statistically significant for the East-Mediterranean region.
Keywords: distribution; ecology; phenology; temperature; Verbascum; PLANTS; SCROPHULARIACEAE; Environmental Sciences & Ecology